2013
DOI: 10.3892/ijmm.2013.1273
|View full text |Cite
|
Sign up to set email alerts
|

EBM84 attenuates airway inflammation and mucus hypersecretion in an ovalbumin-induced murine model of asthma

Abstract: Abstract. EBM84 is a traditional herbal medicine and a combination of extracts obtained from Pinellia ternata and Zingiber officinale. It is traditionally used to treat vomiting, nausea, sputum and gastrointestinal disorders, and functions is an effective expectorant. In this study, we evaluated the protective effects of EBM84 on asthmatic responses, particularly mucus hypersecretion in an ovalbumin (OVA)-induced murine model of asthma. We also analyzed EBM84 composition using high performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Inflammatory reaction is an important cause in the development of asthma, and previous reports also indicated that anti-inflammatory drugs could be beneficial for treating or relieving asthma symptoms [12,13]. In this study, the results showed that IPT possessed significant antiinflammatory effects on airway inflammation induced by OVA via suppression of both inflammatory cells (eosinophils, neutrophils, lymphocytes and macrophages) and cytokines (IL-4, IL-13, IL-6 and TNF-α).…”
Section: Discussionsupporting
confidence: 59%
“…Inflammatory reaction is an important cause in the development of asthma, and previous reports also indicated that anti-inflammatory drugs could be beneficial for treating or relieving asthma symptoms [12,13]. In this study, the results showed that IPT possessed significant antiinflammatory effects on airway inflammation induced by OVA via suppression of both inflammatory cells (eosinophils, neutrophils, lymphocytes and macrophages) and cytokines (IL-4, IL-13, IL-6 and TNF-α).…”
Section: Discussionsupporting
confidence: 59%
“…However, our results showed that MPO activity in the lungs was reduced with ginger treatment. Therefore, we suggest that ginger has antiinflammatory properties by decreasing neutrophil activation and migration into the lungs with evidence of reduced MPO activity in the lungs (9,11). Oxygen toxicity has a key role in the development of BPD (1)(2)(3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 95%
“…Pups in the control group (21% O 2 for 14 days + placebo) and hyperoxia + LPS group (95% O 2 for 14 days + placebo) were administered oral saline (2 mL/kg), but pups in the hyperoxia + LPS + ginger group (95% O 2 for 14 days + ginger) were treated once a day from the first day of the study to the end of the study. In the present experiment, we used whole ginger since many different compounds in ginger have been determined to act in a synergic manner that suggests the importance of using whole ginger (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Preparation and Dosage Of Gingermentioning
confidence: 99%
“…In their research, one of the XQLT ingredients, Pinellaiae ternata, played an important role in decreasing OVA-specific IgE. Lee et al [37] and Shin et al [38] also provided data that Pinellaiae ternata might play a definite role in decreasing Th2 reaction in asthmatic animal models. Pinellaiae ternata is in highest proportion of XQLT components.…”
Section: Discussionmentioning
confidence: 99%